Multi‐criteria hydraulic turbine optimization using a genetic algorithm and trust‐region postprocessing - Rentschler, Tobias; Berkemeier, Manuel Bastian; Fraas, Stefan; Tismer, Alexander; Raj, Rohit; Peitz, Sebastian; Riedelbauch, Stefan (Proceedings in applied mathematics and mechanics, 2024)
A two‐stage, multi‐objective optimization approach is proposed to improve the overall efficiency of the time‐consuming and computationally expensive optimization process for hydraulic turbines. The purpose is to optimize the shape of the turbine blades, designed using 30 parameters, in order to maximize its efficiency and minimize both the cavitation volume and the deviation between the desired and the calculated design head. In the first step of the routine, the genetic algorithm “Non‐Dominated Sorting Genetic Algorithm II (NSGA‐II)” is used to generate an initial approximation of the Pareto front that covers a wide variety of possible solutions, that is, optimal trade‐offs between the conflicting objectives. Subsequently, to ensure convergence, the trust region optimizer “Constrained Multiobjective Problem Optimizer with Model Information to Save Evaluations (CoMPrOMISE)” is used, which is initialized with individuals selected from the Pareto set generated by the genetic algorithm.